2022
DOI: 10.1002/solr.202200021
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Engineering Enables 1.31 V Open‐Circuit Voltage for Efficient and Stable Wide‐Bandgap Halide Perovskite Solar Cells

Abstract: Figure 7. a) Normalized PCE of the unencapsulated devices in the N 2 glove box at 50 C. b) Normalized PCE of the unencapsulated devices under 25% AE 10% relative humidity (RH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The composition of WBG perovskite in this work is Cs 0.2 FA 0.8 Pb(I 0.7 Br 0.3 ) 3 , deposited by a one‐step method. [ 20 ] Its optical bandgap ( E g ) is ≈1.75 eV, as shown in Figure S1 in the Supporting Information. For the FPEAI‐added sample, 1.5 mol% FAI was substituted by FPEAI in the perovskite precursor.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of WBG perovskite in this work is Cs 0.2 FA 0.8 Pb(I 0.7 Br 0.3 ) 3 , deposited by a one‐step method. [ 20 ] Its optical bandgap ( E g ) is ≈1.75 eV, as shown in Figure S1 in the Supporting Information. For the FPEAI‐added sample, 1.5 mol% FAI was substituted by FPEAI in the perovskite precursor.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the unique properties of PEA spacers, 64,65 researchers have explored the molecular structure and extended the use of phenyl spacers such as benzylammonium (BnA), 66 phenylbutylammonium (PBA), 67 4-fluorophen-ethylammonium (FPEA), 68,69 and pentafluorophenylethylammonium (FEA), 32 among others. 33,35,70–74 In 2019, Grätzel et al employed FEA in highly efficient bilayer 2D/3D PSCs and successfully demonstrated the dominant generation of 2D perovskite on the surface of the 2D/3D bilayer through X-ray reflectivity (XRR) and grazing incidence X-ray diffraction (GIXRD) characterization.…”
Section: D/3d Heterojunctions In Mixed Dimensional Perovskite Solar C...mentioning
confidence: 99%
“…In light of the unique properties of PEA spacers, 64,65 researchers have explored the molecular structure and extended the use of phenyl spacers such as benzylammonium (BnA), 66 phenylbutylammonium (PBA), 67 4-fluorophen-ethylammonium (FPEA), 68,69 and pentafluorophenylethylammonium (FEA), 32 among others. 33,35,[70][71][72][73][74] system undergoing photochemical cross-linking under UV photoexcitation (B250 nm) to produce new covalent bonds when forming 2D perovskites.…”
Section: Surface Treatment Modelmentioning
confidence: 99%
“…The general trend observed is that the shunt resistance and V oc of devices decrease with decreasing work function of the back contact. [ 89,96,97 ]…”
Section: General Architecture Of Solar Cellsmentioning
confidence: 99%
“…The general trend observed is that the shunt resistance and V oc of devices decrease with decreasing work function of the back contact. [89,96,97] Concerning the carbon electrode, some strategies have been used to tune the W f and improve the solar cell performance. Thus, CuPc nanoparticles have upshifted the W f of carbon electrodes, increasing the V oc and hole extraction.…”
Section: General Architecture Of Solar Cellsmentioning
confidence: 99%